Pola Komunikasi Orang Tua Dalam Pembentukan Kecerdasan Sosial Di Kalangan Remaja Milenial - Fitri Sayidati Mukaromah; Akif Khilmiyah; Aris Fauzan (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This article aimed to describe communication pattern of parents among millennial adolescents and explain effective specific strategies of parental communication in shaping social intelligence among millennial adolescents. This is a field research that is a descriptive analytic study in nature with a qualitative approach that is ethnographic. Purposive sample was used and the data were collected through interview, observation, and document. The research credibility was done using the triangulation of source and method. The obtained data were then analyzed qualitatively using data reduction, data display, and conclusion drawing.The findings of the research are; firstly, the communication patterns used by family whose background is teachers in Bumirejo village are democratic and permissive communication patterns. Parents who implement democratic communication have communication characteristics such as having an open communication, cooperation, a mutual relation, and socializing with the society and motivating the adolescents. Secondly, in order to have a good communication in a family, some strategies done by the family whose background is teachersin Bumirejo village are such as by having a direct communication via a comfortable approach and by limiting their children’ access in using mobile phones.